Adjusting the Volume: Private‐Activity Municipal Bonds and the Variation in the Volume Cap. (February 2014) - Whitaker, Stephan
<x xml:space="preserve">Abstract</x> States allocate authority, under a federally‐imposed volume cap, to issue tax‐exempt bonds for financing private activities including industrial development, utilities, and low‐income housing. The generosity of the cap varies widely between states. This paper analyzes the relationships between the caps, political characteristics of the states, and the authorizations to competing constituencies. In per capita terms, each additional dollar of volume cap is associated with an additional 0.49 to 0.66 of borrowing per year. Mortgage revenue bonds and student loan bonds are the most responsive to variation in the cap. There is some evidence of political influence on the allocation process.